Cloninger Type 2 Score and Lesch Typology Predict Hospital Readmission of Female and Male Alcohol-Dependent Inpatients During a 24-Month Follow-Up - Weinland, Christian; Braun, Birgit; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Alcoholism-Clinical and Experimental Research, 2017)
BACKGROUND: Relapse after detoxification treatment is a common problem in alcohol dependence. However, its prediction still lacks reliability. We here investigated whether the easily accessible clinical Cloninger and Lesch classifications predict alcohol-related hospital readmission following inpatient withdrawal treatment. METHODS: In this bicentric prospective clinical study, 67 female and 84 male alcohol-dependent inpatients were characterized according to the Cloninger items and the Lesch typology. The patients' records were followed for 24 months. Because of the well-established sex differences in alcohol dependence, we studied females and males separately. RESULTS: Overall, 54% of the female patients and 67% of the male patients sustained at least 1 alcohol-related hospital readmission during the follow-up. Readmission was related to a higher Cloninger type 2 score than nonreadmission (females, p = 0.007, males p = 0.044). In females, the Cloninger type 2 score correlated with the number of readmissions (ρ = 0.384, p = 0.001) and the days to first readmission (ρ = -0.333, p = 0.006). The effects were stronger in patients with age at onset of alcohol dependence over 25 years. We found gender dimorphisms concerning the Cloninger items. In female patients, the 4 Lesch subtypes differed in their risk (p = 0.010), the number (p = 0.040), and the days to first readmission (p = 0.031). Lesch type 1 was associated with an increased risk (OR = 4.83, p = 0.041) and Lesch type 2 with a reduced risk (OR = 0.07, p = 0.004). In addition, the number of previous inpatient alcohol withdrawals predicted the patients' outcomes (p < 0.05). CONCLUSIONS: The Cloninger type 2 score and the Lesch typology are promising tools for the prediction of alcohol-related readmissions. Our findings provide the basis to optimize relapse prevention in alcohol dependence.
EVALuna2:33401